LEGAL PRINCIPLES IN FUNCTION AND PERFORMANCE OF BOT CONTRACT - Reifon Cristabella Eventia (Yuridika, 2017)
Build, Operate and Transfer (BOT) represents a long term partnership of the government and private sector. In BOT project, either the government or a private sector identifies a need for a development project. The philosophy in BOT contract begins from the increasing infrastructural needs in all areas and with a limited budget, government are required to commit the duties and functions state governance so that the concept of BOT give a solution through a partnership with the private sector. The government then gives a concession to the private sector to build the project and operate it for a fixed period years, after the period ended, the building shall be transferred to the government. Through BOT, the country is able to gain asset without government spending while maintaining a measure of regulatory control over the project. BOT permits the government to use private sector fund to finance public infrastructure development. The main issues elaborated in this article are the legal principle in the formation of BOT contract and the legal principle in the performance of BOT contract. There are two results; firstly, in the formation of a BOT contract, the principles of partnership and the principle of transparency should be emphasized. Secondly, in performance of the BOT contract, the principle of risk management and the principle of proportionality should be clearly stated in the rules and legal norms.